A Study Of Risk And Market Segmentation In The Returns Of Financial Intermediaries In Malaysia - Hassan, Syara Syafrina (2004)
The purpose of this study was to examine if market segmentation existed among the various groups of financial intermediaries with regards to risk return characteristics.